ALIGNING IT COMPONENTS TO ACHIEVE AGILITY IN GLOBALLY DISTRIBUTED SYSTEM DEVELOPMENT. - ONE-KI LEE, DANIEL; BANERJEE, PROBIR; LIM, KAI H.; KUMAR, KULDEEP; HILLEGERSBERG, JOS VAN; KWOK KEE WEI (Communications of the ACM, 2006)
The article focuses on how international business enterprises can manage their globally distributed system development (GDSD). The authors provide a case study of how the Swedish company Skandia, which is a global leader in the field of life and casualty insurance, created an Internet portal for its clients in various countries in cooperation with the consulting firm Tata Consultancy Services. Skandia was able to create different Internet portals for clients in different countries though the use of an IT "component" approach, which simplified software development by allowing each Web site to be built using a largely common architecture.